The impact of preparatory work for mega sports events on carbon emissions: a case study of the Beijing Winter Olympics - Huang, Junpei; Lin, Ruofei (Frontiers in Environmental Science, 2025)
Mega Sports Events draw global attention and engagement but also result in substantial environmental costs, primarily through significant carbon emissions generated during the preparatory phase. This research specifically examines the carbon emissions associated with the preparation stage of international Mega Sports Events, assessing their environmental impacts and exploring effective strategies for mitigation. Using the 2022 Beijing Winter Olympics as a case study, this paper employs the Synthetic Control Method (SCM) and the Logarithmic Mean Divisia Index (LMDI) to analyze the impact of the Olympic preparations on Beijing’s carbon emissions. The findings indicate that from 2015 to 2022, the preparations contributed approximately 118 million tons of additional carbon emissions. The emission rate initially rose but subsequently decreased, corresponding to the completion of major infrastructure projects for the event. The LMDI decomposition highlights that economic activities spurred by the Olympics primarily drove these emissions.